The Intersectoral Linkage Effects in Turkish Economy: An Application of Static Leontief Model - Yay, Guelsuen Guerkan; Keceli, Serkan (SAVEZ EKONOMISTA VOJVODINE, 2009)
In this study, the leading activities of Turkish Economy whose changes in their structure of production, value-added and employment are interrelated with the other activities of the economy, are found by using the input-output model which is presented and called as an 'Application of the General Equilibrium Theory' by Leontief. For this purpose; firstly theoretical foundations of the input-output model are examined. After that, 59 activities of the 2002 Input-Output Table of the Turkish Economy are aggregated at 52 sectors and classified into three categories as Ricardo Sectors, High-Technology Sectors and Heckscher-Ohlin Sectors like Dasgupta and Chakraborty did for the Indian Economy in 2005. Then, the leading, key or strong activities of the economy that are more interrelated with other activities are calculated and found by the Static Leontief Model which is used by the Traditional Methods as the techniques to calculate the linkage effects like Chenery-Watanabe and Rasmussen methods to determine the sectors having the highest priority at investment policies according to the Hirschmanian Unbalanced Growth Model. As a result of the interpretation of Leontief Model, using the traditional methods of Chenery-Watanabe and Rasmussen while calculating the linkage effects rather than the hypothesis extraction methods like Strassert's Original Extraction Method, Cella's Extraction Method, Sonis' Pure Linkage Method and Dietzenbacher and Van der Linden's Method or a SAM (Social Accounting Method) model which does not omit the income generating process (distributing income among primary factors and households as a result of production) of a sector, in Turkey, the Heckscher-Ohlin Sectors mostly seen in the manufacturing industry which Kaldor refers as the engine of growth, are stronger than the other sectors.
Keywords: Leontief Input-Output Model; Ricardo Sectors; Heckscher-Ohlin Sectors and High-Technology Sectors; General Equilibrium Analysis; Multiplier Analysis; INPUT-OUTPUT-ANALYSIS; GROWTH; Business & Economics